THE INFLUENCE OF DIET HABITS, ON WHAT, HOW, HOW MUCH AND FOR WHOM TO PRODUCE IN THE AGRICULTURAL SECTOR OF SERBIA? - Vujović, Slavoljub Mirko; Cvijanović, Dušica; Vujić, Nenad (Economics of Agriculture, 2020)
The assumption that the questions of what, how, how much and for whom to produce are of paramount importance for all producers in the agricultural sector of Serbia, is the reason for researching the relationship between socio-demographic variables income of the respondents household, the number of household members and the number of household members earning income) and eating habits, in order to collect information on what the population of Serbia consumes or wants to consume, and in what quantities.